Predictive value of health-related fitness tests on mobility difficulties in high-functioning older adults - Husu, Pauliina; Tampere University Press (Acta Universitatis Tamperensis, ISSN 1455-1616, 2008)
Tiivistelmä.
Keywords: liikkuminen; liikuntakyky; ennustettavuus; ikääntyneet; kuntotestit; testit